Integrating Environmental Science and the Economy: Innovative Partnerships between the Private Sector and Research Infrastructures - Chabbi, Abad; Loescher, Henry W.; Dillon, Margaux S. (Frontiers in Environmental Science, 2017)
The present paper is a preliminary analysis of the funding, organizational culture, environmental and innovation challenges that are currently faced by Environmental Research Infrastructures (ERI) and private enterprises working together. We contend there is a strong case for building creative collaboration models across these sectors that also require to new management tools to effectively generate economically-driven solutions to the global society at large in the face of climate change. To that end, public/private stakeholders that are likely to partner to address climate change also face new frontiers in how they will structurally and organizationally work together. We explore these issues around changing political, scientific, commercial environments; partnerships models; barriers in bridging these communities; and the role of formal project management processes. There is no one solution to fit all conditions that can bring together a specific public / private enterprise that incorporates a research infrastructure. However, we have provided two examples of collaborative models of public/private enterprises to highlight how these issues can be addressed, and to foster future dynamic and creative solutions to this problem.